LEARNING BY DOING MEDIA BELAJAR JAM DINDING DALAM PEMBELAJARAN MATEMATIKA DI KELAS 2 MIN 3 BANYUMAS - Faujatun Nahdiyah (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The research was carried out the lock of student’s abilities in understanding time unit. Time unit is abstract, so it’is needed real object as a model to make the student understand easily.in other hand, the student should be given real activity that can be recreved easily. In order to make them understand the concept of time unit.The success of a teaching and learning process is one of the reasons due to the use of media or participation in the teaching and learning process. Because in the teaching and learning process media has an important meaning.This research used a qualitative method, and used wall clock that made by paper carton. With a wall clock made of cardboard, it is easy for students to use the clock by rotating the direction of the needle on the cardboard between the long needle and the short needle must match.